Encapsulation of ascorbic acid with highly branched corn starch and its release behaviors - Gu, Zixuan (fi=Turun yliopisto|en=University of Turku|, 2018)
Ascorbic acid (AA) is of significant functionality in human life, but it is unstable in the aqueous. Aiming at increasing the stability of AA and making full use of its bioactivity, in this study, dual-enzymatic modification of high amylose corn starch (HACS) was adopted to gain the embedding vector, highly branched corn starch (HBCS), for encapsulating AA. The highly branched corn starch - ascorbic acid (HBCS-AA) inclusion complex was characterized and its release behavior was also investigated. The results showed that the ratio of alpha-1, 6 glycosidic bonds increased by 1.93% after modification and a compact branched configuration of HBCS was formed in the aqueous phase, which was a good highly branched carrier. DSC results demonstrated the conformation of HBCS-AA inclusion complex. The controlled release behavior in stimulated gastric fluid indicated the release of HBCS-AA obeyed the Fick diffusion mechanism and followed first - order kinetic model. Meanwhile, the photo-stability and thermo-stability of embedded AA were both enhanced compared with pure AA.